Tax-Bbased modeling of Zakat compliance - Sanep Ahmad; Nor Ghani Md Nor; Zulkifli Daud (Penerbit Universiti Kebangsaan Malaysia, 2011)
This study aims to formulate of model zakat compliance for formal zakat collection institutions based upon tax compliance model. the study further conducts an empirical examination of the application of the model developed utilizing a case study on the province of Acheh. The Study demonstrates that it is possible to construct a zakat compliance model based upon the tax compliance model.The case study of Acheh also suggests that individual zakat compliance was not significantly influenced by zakat law, but by factors of demography (gender and age)referencegroup, education, and the perception on the tax system.